Pengaruh Gaya Kepemimpinan Dan Insentif Yang Diberikan Terhadap Kinerja Kerja Karyawan PT. Multi Aneka Pangan Nusantara Di Gresik - Iklima Adilvi Artafilah; Achmad Daengs GS; Harsono Teguh S; Bambang Karnain; Sugiharto Sugiharto (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to observe and analyze the influence of leadership style and incentives given to the performance of employees of PT. Multi Aneka Pangan Nusantara in Gresik Partially and simultaneous. This research method tends to be descriptive and tends to be general. Data obtained directly from the respondent or the object under study or something to do with the object under study. This data can be in the form of interviews, questionnaires, and observations that will be carried out at PT. Multi Aneka Pangan Nusantara Gresik. As for secondary data obtained from books, journals, and other related sources and strengthen the basis of research and written sources that refer to existing theories. The data analysis technique used in this study was multiple linear analysis, t test and F test. The results showed that Leadership Style (X1) had a positive and significant effect on the performance (Y) of employees at PT. Multi Aneka Pangan Nusantara is proven by t count -0.910 with a significance of 0.037. Incentives (X2) have a positive and significant effect on the performance (Y) of employees of PT. Multi Aneka Pangan Nusantara is proven by a t count of 4.571 with a significance of 0.000. PT employees Multi Aneka Pangan Nusantara Leadership style (X1), incentives (X2) have a positive and significant impact on the performance (Y) of employees of PT. Multi Aneka Pangan Nusantara is proven by f count 10.315 with a significance of 0.000. Positive influence in this sense means that if the employee's perception of the leader's attitude is getting better, then the performance of the employees will also be getting better. Likewise, the higher the incentive, the better the employee performance.